Integration of Individual Processes and Information Demand Patterns: A Conceptual Analysis - Michael Leyer; Kurt Sandkuhl (Complex Systems Informatics and Modeling Quarterly)
Individuals need a variety of information when performing their personal processes. However, companies typically know little about the underlying individual demand patterns in these processes. Conceptualizing information demand patterns of individuals is expected to allow for using these as foundation to extend the traditional internal information logistic perspective of companies. Digital options could then be used to align individual and organizational information leading not only to new product and service offers, but also to new work structures in organizations. Thus, we extend prior literature regarding business process management and information logistics by highlighting how information demand patterns (IDP) have to be adapted to individual processes. Our exploratory approach is to demonstrate conceptually the conditions and implications of individual IDPs.